Aetiology and Outcomes of Suspected Infections of the Central Nervous System in Children in Mbarara, Uganda - Page, Anne-Laure; Boum, Yap; Kemigisha, Elizabeth; Salez, Nicolas; Nanjebe, Deborah; Langendorf, Céline; Aberrane, Said; Nyehangane, Dan; Nackers, Fabienne; Baron, Emmanuel; Charrel, Rémi; Amumpaire, Juliet Mwanga (Scientific reports, 2017)
Infections of the central nervous system (CNS) are severe conditions, leading to neurological sequelae or death. Knowledge of the causative agents is essential to develop guidelines for case management in resource-limited settings. Between August 2009 and October 2012, we conducted a prospective descriptive study of the aetiology of suspected CNS infections in children two months to 12 years old, with fever and at least one sign of CNS involvement in Mbarara Hospital, Uganda. Children were clinically evaluated on admission and discharge, and followed-up for 6 months for neurological sequelae. Pathogens were identified from cerebrospinal fluid (CSF) and blood using microbiological and molecular methods. We enrolled 459 children. Plasmodium falciparum (36.2%) and bacteria in CSF (13.3%) or blood (3.3%) were the most detected pathogens. Viruses were found in 27 (5.9%) children. No pathogen was isolated in 207 (45.1%) children. Patterns varied by age and HIV status. Eighty-three (18.1%) children died during hospitalization, and 23 (5.0%) during follow-up. Forty-one (13.5%) children had neurological sequelae at the last visit. While malaria remains the main aetiology in children with suspected CNS infections, no pathogen was isolated in many children. The high mortality and high rate of neurological sequelae highlight the need for efficient diagnosis.
Keywords: Aetiology; Suspected Infections; Nervous System; Infections of the central nervous system; admission and discharge; bacteria; high mortality